"Dear Colleague" letter from 2011 SAMHSA still valid. Issue 10 (6th March 2021) - Knopf, Alison
Abstract : The 2011 "Dear Colleague" letter to Opioid Treatment Programs (OTPs) requiring them to check with Prescription Drug Monitoring Programs (PDMPs) but banning them from putting patient information into them is still valid, ADAW has learned. Despite confusion caused by discussions about eliminating 42 CFR Part 2, the confidentiality regulation, there is no confusion about what OTPs should do in terms of PDMPs. A spokesman for the Substance Abuse and Mental Health Services Administration (SAMHSA) told ADAW last week that the letter is still valid.